Business and Marketing Analysis of Coconut Sugar Agro-Industry Crafters in Ciracap District, Sukabumi Regency - Srimarliani, Yosi; Dasipah, Euis; Gantini, Tuti (Universitas Majalengka, 2024)
This study aims to analyze the income of coconut sugar agroindustry craftsmen and determine the marketing efficiency of coconut sugar in Ciracap District, Sukabumi Regency, West Java Province. The use of business analysis and marketing analysis is the method chosen to find out how much income is earned by craftsmen and how much marketing efficiency has been carried out on the coconut sugar marketing chain in this area. Business analysis can be seen through the calculation of cost analysis, the results of the calculation of revenue, and the amount of income. Marketing analysis is obtained by looking at the efficiency of marketing channels, calculating marketing margins, and looking for the farmer's share value so that it is obtained how efficient the marketing flow has been by coconut sugar marketing actors. From the results of research that has been done, it can be seen that the average production cost of coconut sugar craftsmen is Rp. 4. 692,194 per month, the average income of the craftsmen Rp. 6,754,762 per month and the average monthly income of crafters is Rp.2,062,567 so that the R/C ratio obtained is 1.43. There are three patterns of coconut sugar marketing channels, namely marketing channel pattern 1, marketing channel pattern 2, and marketing channel pattern 3. Marketing channel pattern 3 is the most efficient marketing channel pattern in the coconut sugar marketing system in the research area. The total marketing margin generated in the pattern of marketing channels 1 and 2 is Rp. 6,054, and in channel 3 is Rp. 8,054, with farmer's share of 76.92%, 84.61%, and 66.67% for marketing channel patterns 1,2, and 3.